Notes on life history and field efficiency of Cybocephαlus fodori predator of Quαdrαspidiotus perniciosus in Northern Greece - Katsouannos Ρ. (ENTOMOLOGIA HELLENICA, 1984)
Sampling results during 1978-1979 and 1981-1982 in two heavily-infested almond orchards in Northern Greece showed a high mortality of the San Jose scale. A considerable part of this mortality was attributable to indigenous entomophagous insects, especially predators. Among them, Cybocephalus fodori Endrody-Younga (Coleoptera: Nitidulidae) appeared to be the key species. Field observations showed that C. fodori hibernates as an adult, forming aggregations. C. fodori reared in outdoor cages showed full adult activity by end March. Given an abundant supply of prey, the insect develops two complete and a third partial generations per year. Under constant conditions (25±2° C, 65±5% R.H. and 16 hrs light per day), the development of its three larval instars was completed in about 19 days and the pupal stage lasted about 10 days. On average, 68 Quadraspidiotus perniciosus Comstock (Homoptera: Diaspididae) adult females were partly consumed per larva of C. fodori. Individually deposited eggs and young larvae were found under the covers of the San Jose scales.